2019
DOI: 10.3390/brainsci9120336
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Neighbor Housing Environment Enhances Social Interaction and Rescues Cognitive Deficits from Social Isolation in Adolescence

Abstract: Adolescence is characterized by high levels of playful social interaction, cognitive development, and increased risk-taking behavior. Juvenile exposure to social isolation or social stress can reduce myelin content in the frontal cortex, alter neuronal excitability, and disrupt hypothalamic pituitary adrenal (HPA) axis function. As compared to group housed animals, social isolation increases anxiety-like phenotypes and reduces social and cognitive performance in adulthood. We designed a neighbor housing enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 45 publications
2
16
1
Order By: Relevance
“…This increased anxiety was further supported by social dominance as measured by the tube test 10 . The most surprising finding in this study was that, in contrast to previous studies 8,9 , divided housing caused even higher anxiety levels than single housing. These results implied that sensing other social signals without direct physical interaction may produce an even more stressful environment than complete social isolation.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This increased anxiety was further supported by social dominance as measured by the tube test 10 . The most surprising finding in this study was that, in contrast to previous studies 8,9 , divided housing caused even higher anxiety levels than single housing. These results implied that sensing other social signals without direct physical interaction may produce an even more stressful environment than complete social isolation.…”
Section: Discussioncontrasting
confidence: 99%
“…Unexpectedly, our experiment did not detect a significant difference between single-housed and pair-housed mice in either anxiety-or depressionlike behavior. Although it is generally believed that anxiety and depression can be induced by social isolation, this relationship has not always been consistent in mouse studies 8,9,15,16 . Failure to detect the difference might be due to the shorter isolation time or larger isolation space in our experimental designs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…or vehicle and immediately returned to their home cage. Preference for light or dark environment as a proxy for anxiety-like behaviors was assessed 18h after drug administration using a commercial open field in which space is equally divided into light and dark areas (25 × 12 × 20 cm each) connected through a small (5 × 5 cm) opening ( 67 ). The tracking system (Fusion v5.3; Omnitech Electronics Inc.) infers animal activity and position from interruptions to infrared beams traversing the different planes of space.…”
Section: Methodsmentioning
confidence: 99%
“…Another study found that developmentally isolated adult female mice take longer than socially-housed mice to learn an operant task, though after training they did not show reduced performance on a USV discrimination task (Screven and Dent, 2019). Notably, one study suggests that the effects of adolescent social isolation may be ameliorated by partial indirect social housing, holding promise for future study (Pais et al, 2019).…”
Section: Impact Of Social Isolation During Developmentmentioning
confidence: 99%